TEACHER LEARNING IN CONTEXTS OF POLICY IMPLEMENTATION - Msomi, W. N.; Van der Westhuizen, G. J.; Steenekamp, K (South African Journal of Higher Education, 2016)
Teacher education needs to be viewed as a continuum that begins with pre-service learning, followed by teacher induction, and then the continuing professional development (CPD) of teachers. To date researchers know much less about teacher induction relative to the other two phases of teacher education, in part because of its informal nature in most schools. Ethiopia is one of few exceptions in the world that has recently introduced an institutionalised and formal multi-year programme of induction for beginning teachers. This paper examines the organisation and practice of teacher induction in Ethiopia by exploring the experiences of three first year primary school teachers. Our findings suggest that while the structure and organisation of the mentoring programme are similar across schools, the professional guidance and assistance that is offered to the first year teachers varies greatly depending on a number of factors. We conclude with a discussion of the need to re-examine the conditions of implementations of the induction programme. Without proper resources, mentors, time allocated, and regular on-site monitoring, the formal teacher induction programme is unlikely to realise its intended benefits of supporting beginning teachers with adequate subject knowledge and skills required for quality teaching in the schools.